Effect of Biotechnological Fermentation Waste Kombucha Flower Telang (Clitoria ternatea L) as Liquid Fertilizer on The Growth of Sawey (Brassica chinensis var. parachinensis) - Hari Hariadi; Firman Rezaldi; Fajar Hidayanto; Ade Sumiardi; Mu'jijah Mu'jijah; Muhammad Faizal Fathurrohim; Yuliana Kolo; Syariful Mubarok (Jurnal Biologi Tropis, 2023)
Liquid organic fertilizer comes from nature and has the potential to improve biological, physical and soil properties because it contains nutrients that have the potential to increase plant growth. This research was conducted to determine liquid fertilizer made from telang kombucha fermentation waste on the growth of mustard plants. The method used was a completely randomized design with a single factor, namely the difference in the concentration of liquid organic fertilizer given 6 treatments with 5 replications for each treatment. The research data were analyzed statistically through ANOVA at a significance level of 95%. Parameters in this study were plant height, number of leaves, fresh weight and dry weight. The results of this study prove that the spraying treatment of liquid organic fertilizer containing kombucha fermentation waste of butterfly pea flowers has an effect on the growth parameters of mustard plants. The conclusion is that liquid organic fertilizer from the waste of fermented kombucha flower butterfly pea at a concentration of 5 mL/L can increase plant height, number of leaves, wet and dry weight of mustard plants.